Near-inertial motions in the DeSoto Canyon during Hurricane Georges. (September 2016) - Jordi, Antoni; Wang, Dong-Ping; Hamilton, Peter
Highlights: Inertial motion generated by Hurricane George in the DeSoto Canyon is analyzed. Data from 13 mooring and a realistic primitive-equation model are used. Strong inertial motions were present in the mixed layer in the open ocean. Inertial waves trapped in an energy flux recirculation gyre around the canyon. The gyre transferred 1/3 of the wind input below the mixed layer. Abstract: Hurricane Georges passed directly over an array of 13 moorings deployed in the DeSoto Canyon in the northern Gulf of Mexico on 27–28 September 1998. Current velocity data from the mooring array were analyzed together with a primitive-equation model simulation with realistic hurricane forcing, to characterize the generation and propagation of the hurricane-generated near-inertial waves. The model successfully reproduces the observed mean (sub-inertial) and near-inertial motions. The upper ocean response is strongly impacted by the canyon 'wall': a strong jet is formed along the slope, and the near-inertial motions on the shelf are rapidly suppressed. The model results moreover suggest that strong near-inertial waves in the mixed layer are mostly trapped in an energy flux recirculating gyre around the canyon. This gyre retains the near-inertial energy in the canyon region and enhances the transfer of near-inertial energy below the mixed layer. Additional simulations with idealized topographies show that the presence of a steep slope rather than the canyon is fundamental for the generation of this recirculating gyre. The near-inertial wave energy budget shows that during the study period the wind generated an input of 6.79 × 10 –2 Wm –2 of which about 1/3, or 2.43 × 10 –2 Wm –2, was transferred below the mixed layer. The horizontal energy flux into and out of the canyon region, in contrast, was relatively weak.